Reading comprehension and its relationship to the development of listening and speaking skills for fourth year middle school students - Huda Hamid Mustafa, Lect. Dr. (lark, 2022)
The current research aims to identify reading comprehension and its relationship to the development of listening and speaking skills for fourth-year middle school students. The research was limited to the students in the fourth year of middle school in the morning schools of the General Directorate of Education in Baghdad. Rusafa the first, numbering 120 students they were chosen randomly. To achieve the goal of the research, the researcher adopted a test (Abu Hamra, 2015). Which in its final form consists of (50) paragraphs of the type of multiple-choice, the student gets one point for each correct answer to the question.   , and get a score of zero in the case of the wrong answer. After verifying its validity and reliability, it was applied to the research sample and the data were collected and processed statistically by using the appropriate statistical methods زThe results of the research revealed that there was a statistically significant relationship at the level (0.05) of reading comprehension with the development of the listening and speaking skills of the sample students And it was found that the female students who were included in the current research were characterized by speaking skill that tends towards the middle or a little more than it. This indicates a strong correlation between the three variables addressed in the current research .A number of recommendations and proposals were formulated, including training students on speaking and listening skills in proportion to their mental abilities and developing a test to measure the four language arts (listening, speaking, reading, and writing)
Keywords: Keywords: reading comprehension, listening skill, speaking skill, fourth grade of middle school, descriptive-associative approach. Keywords: reading comprehension, listening skill, speaking skill, fourth grade of middle school, descriptive-associative approach.